2013
DOI: 10.1371/journal.pone.0054320
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component System Response Regulators Involved in Virulence of Streptococcus pneumoniae TIGR4 in Infective Endocarditis

Abstract: Streptococci resident in the oral cavity have been linked to infective endocarditis (IE). While other viridans streptococci are commonly studied in relation to IE, less research has been focused on Streptococcus pneumoniae. We established for the first time an animal model of S. pneumoniae IE, and examined the virulence of the TIGR4 strain in this model. We hypothesized that two-component systems (TCS) may mediate S. pneumoniae TIGR4 strain virulence in IE and examined TCS response regulator (RR) mutants of TI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…However, in the context of IAV infection, the hk01::ery mutant showed impaired pneumococcal intracellular survival compared to the wt strain ( Fig 1B), suggesting that their components participate in sensing the IAV-infected environment. The hk01:: ery mutant corresponds to TCS01, one of the least studied TCSs but previously identified as a virulent factor in S. pneumoniae [23][24][25]. TCS01, hereafter named SirRH (for stress-induced response), contains the SirH histidine kinase and the SirR response regulator.…”
Section: The Sirrh Two-component System Mediates Enhanced Pneumococcamentioning
confidence: 99%
“…However, in the context of IAV infection, the hk01::ery mutant showed impaired pneumococcal intracellular survival compared to the wt strain ( Fig 1B), suggesting that their components participate in sensing the IAV-infected environment. The hk01:: ery mutant corresponds to TCS01, one of the least studied TCSs but previously identified as a virulent factor in S. pneumoniae [23][24][25]. TCS01, hereafter named SirRH (for stress-induced response), contains the SirH histidine kinase and the SirR response regulator.…”
Section: The Sirrh Two-component System Mediates Enhanced Pneumococcamentioning
confidence: 99%
“…S. pneumoniae has 13 complete TCSs and an orphan regulator (RR14, RitR) [14][15][16]. Previous studies have shown that most of the TCSs are necessary for pneumococcal pathogenicity in animal models [15,17], but the precise functions for most of the TCSs are largely unknown.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Therefore, the Pst1 and Pst2 transporters must mediate P i acquisition from several niches with vastly different P i concentrations in human hosts (Orihuela et al, 2001 ; Wilson, 2005 , 2008 ). Signature-tagged mutagenesis (STM) screens and a study of the role of the PnpR RR (also called RR04) indicated that the pnpRS, pst1 , and pst2 operons are all required for full pneumococcal virulence (Polissi et al, 1998 ; Throup et al, 2000 ; Hava and Camilli, 2002 ; McCluskey et al, 2004 ; Paterson et al, 2006 ; Trihn et al, 2013 ). Consistent with these earlier studies, a recent Tn-Seq study showed that PhoU1 is important for nasopharynx colonization, whereas PhoU2 is important for lung infection (van Opijnen and Camilli, 2012 ).…”
Section: Introductionmentioning
confidence: 99%